2014
DOI: 10.1088/1367-2630/16/3/033029
|View full text |Cite
|
Sign up to set email alerts
|

Formation and interaction of resonance chains in the open three-disk system

Abstract: In ballistic open quantum systems, one often observes that the resonances in the complex-energy plane form a clear chain structure. Taking the open three-disk system as a paradigmatic model system, we investigate how this chain structure is reflected in the resonance states and how it is connected to the underlying classical dynamics. Using an efficient scattering approach, we observe that resonance states along one chain are clearly correlated, while resonance states of different chains show an anticorrelatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 80 publications
1
22
0
Order By: Relevance
“…These theoretical findings have been confirmed experimentally in GaAs/AlGaAs (Harayama et al, 2003), GaAs and polymer microstadia . The observation of localization along multiple periodic orbits is consistent with a recent study of an open three-disk system (Weich et al, 2014) which relates this phenomenon to the formation and interaction of resonance chains in the complex frequency plane.…”
Section: Dynamical Localization and Scar Modessupporting
confidence: 90%
“…These theoretical findings have been confirmed experimentally in GaAs/AlGaAs (Harayama et al, 2003), GaAs and polymer microstadia . The observation of localization along multiple periodic orbits is consistent with a recent study of an open three-disk system (Weich et al, 2014) which relates this phenomenon to the formation and interaction of resonance chains in the complex frequency plane.…”
Section: Dynamical Localization and Scar Modessupporting
confidence: 90%
“…By this approach, in [6] resonance distributions were compared to the existent conjectures. Those investigations also revealed the striking formation of resonance chains, which triggered further numerical [2,35] and mathematical [34] studies.…”
mentioning
confidence: 75%
“…The existence of these open conjectures motivated Borthwick to study the resonance spectrum on infinite volume hyperbolic surfaces numerically [4] and to a great surprise he observed that the resonances on 3-funneled Schottky surfaces are often highly ordered and form resonance chains. It has recently been shown in a numerical study by Barkhofen, Faure and the author [1] that these resonance chains can be understood by a generalized zeta function and are related to a clustering of the length spectrum on X and that the same kind of resonance chains also appear in various other physical systems (for details on the significance of resonance chains in physics we refer to [30] and references therein).…”
Section: Introductionmentioning
confidence: 99%